Multidrug-resistant protein inhibitor and phosphodiesterase inhibitor potentiate the vasodilator effect induced by photobiomodulation in isolated aortic rings - de Moraes, Luis Henrique Oliveira; Terroni, Barbara [UNESP]; da Silva Mayer, Nayara Formenton; Rodrigues, Gerson Jhonatan (Springer Nature, 2022)
A previous work indicates that the red LASER (660 nm) induces vascular relaxation by nitric oxide (NO)–dependent mechanism. NO activates soluble guanylate cyclase (sGC) which produces cGMP, the main effector in the vasodilation pathway. An interesting pharmacological strategy is to control the levels of intracellular cGMP, preventing its efflux (with multidrug-resistant protein blockers, such as MK-571), or preventing its degradation (such as sildenafil, which inhibits the enzyme responsible for cGMP degradation, the phosphodiesterase-5 PDE5). This study aimed to look for pharmacological strategies to improve vasodilation LASER effect in normotensive and hypertensive rats (l-NAME model). The vascular reactivity study was performed in isolated aortic rings from normotensive and hypertensive rats, with a single LASER application and sodium nitroprusside (SNP) treatment. In aortic rings from normotensive rats, MK-571 and sildenafil potentiated the relaxation induced by LASER, compared to control. The vasodilation induced by SNP was potentiated by MK-571 and sildenafil, compared to control. In aortic rings from hypertensive rats, vasodilation effect induced by LASER and by SNP was potentiated just by MK-571, compared to control, with no potentiation by sildenafil. In addition, it was seen that the withdrawal of nitric oxide stocks carried out by l-cysteine is capable of being reversed with the use of the SNP. The results support the evidence that the vasodilation induced by red LASER is potentiated by MK-571 and sildenafil in aortic rings from normotensive rats. However, in aortic rings from l-NAME hypertensive rats, the potentiation in vasodilation was induced just by MK-571.
Keywords: Hypertension; LASER; MRP; PDE5; Pharmacological strategies; Vasodilation